Zanthoxylum rhetsa (Roxb.) DC: A systematic review on traditional uses, phytochemistry, and pharmacology. - Farina Aziz; Fahad Imtiaz Rahman; Sumaiya Huque; Sadia Afruz Ether; Choudhury Mahmood Hasan; Monira Ahsan (GarVal Editorial Ltda., 2022)
Context: Zanthoxylum rhetsa (Roxb.) DC is a plant rich in essential oils, terpenes, coumarins, and alkaloids, among others, and has traditionally been used by tribal healers for decades. But as yet, there is no systematic and critical review on this plant to document the phytochemistry and pharmacological properties of its isolated compounds. Aims: To systematically review reports about the ethnobotany, phytochemistry, pharmacological effects and clinical trials of the plant. It also attempts to provide critical assessment of the existing knowledge and research gaps. Methods: Science Direct, PubMed, Wiley Online Library, and Google Scholar were used to collect the relevant research performed on Z. rhetsa, and the discussed dataset finally included 48 articles. Results: The plant has been used traditionally to treat fever, pain, dysentery, cholera, eczema, and rheumatism, among others. Z. rhetsa was found to be abundant in terpenes, coumarins, lignans, alkaloids with broad pharmacological effects, including anti-photo aging, antimicrobial, anti-inflammatory, cytotoxic, antidiarrheal, anthelmintic activities. Studies also revealed its potential use as a food supplement rich in ALA and a functional ingredient in food as a spice. Most pharmacological studies were grounded on crude extracts of the plant, and there is a lack of evidence-based bioactivity-guided research to identify the bioactive compounds. Several research priorities have also been identified, which need to be addressed in the future. Conclusions: Overall, the review attempts to critically assess the existing knowledge and research gaps that can contribute toward improving the prospect of Z. rhetsa as a source of lead molecules in drug discovery.